STROKE RISK ANALYSIS AND INTELLIGENT NUTRITION SYSTEM - George Joseph, S.S.Saranya, Bidusmita Das (International Journal of Advanced Science and Technology, 2020)
In a country with over 5.5% of its population (nearly 73 million) living in conditions of extreme poverty, healthcare seems to be a luxury rather than an easily accessible necessity. Despite the hard times India is also second in the world, after China, to have the most number of internet users [2]. Creating a self care healthcare tool that can be easilyshared via the internet, which can be used to assess the factors that affect stroke health and employing an intelligent lifestyle system to provide nutritional and lifestyle changes to study Stroke HealthinIndiaisofutmostimportance.